Cost-effectiveness analyses alongside randomised clinical trials. - Gray, A (2006)
BACKGROUND: Many health economists increasingly advocate the use of model-based evaluations rather than trial-based evaluations. PURPOSE: The purpose of this paper is to review the merits and limitations of RCT-based evaluations of cost-effectiveness. RESULTS: The paper draws on the examples of large studies such as the United Kingdom Prospective Diabetes Study and the Heart Protection Study to suggest that large randomised trials offer a number of advantages to health economists wishing to estimate cost-effectiveness, including access to patient-level data, unbiased estimates of resource use as well as effects, the estimation of cost-effectiveness in sub-groups of patients, and an enhanced ability to build and validate extrapolation models. CONCLUSIONS: While many methodological issues remain to be resolved, the use of patient-level data derived from clinical trials as a basis for economic evaluations is likely to remain an important part of the health economics evidence base, and will also continue to provide the data required for methodological research.